ANALISIS KESALAHAN SISWA DALAM MENGERJAKAN SOAL CERITA MATEMATIKA BERDASARKAN TIPE NEWMAN PADA KELAS IV SD SE-GUGUS 1 KECAMATAN MARPOYAN DAMAI PEKANBARU - Elsa Ferwinda; Syahrilfuddin Syahrilfuddin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This research is motivated by the number of students who have difficulty in working on mathematical story problems. Students' difficulties in working on the problem indicate that there are errors in the teaching and learning process so that improvements are needed. This study aims to determine student errors that often occur in working on mathematical story problems based on Newman's type. The method used in this research is quantitative descriptive. This research was carried out in several schools included in cluster 1 of the MarpoyanDamai District in Pekanbaru. The sample in this study amounted to 74 people. Based on the results of the study, the most frequent errors made by students in working on mathematical story problems were transformation errors with a percentage of 22%, followed by 15% answer error, 14% error understanding, and 13% process skill errors. If the total number of student errors is totaled, which is 65%, this number is included in the category of very high errors because the percentage is> 55%.